Development of Guided Inquiry-Based E-Module on Human Circulatory System Material to Train Scientific Literacy of 11th Grade High School Students. - Diah Susanti; Zulfiani (Quagga: Jurnal Pendidikan dan Biologi, 2025)
One of the essential skills needed in the development of the 21st century is scientific literacy Therefore, the learning process needs to integrate appropriate teaching models and materials to help students develop scientific literacy, one of which is a guided inquiry-based e-module. This study aims to develop a guided inquiry-based e-module on the human circulatory system to enhance students' scientific literacy. The research methodology used is development research with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research results were obtained through expert validation tests, readability tests, teacher and student response tests, and scientific literacy ability tests. The overall validation test achieved a percentage of 88.22% (highly feasible). The student readability test achieved a percentage of 97.70% (highly readable). The teacher and student response tests received ratings in the excellent category. Additionally, the scientific literacy test results showed an average score of 61 (moderate) for all students, and an average score of 62.36 (moderate) based on scientific literacy indicators. Overall, this study concludes that the guided inquiry-based e-module on the human circulatory system is suitable for use in the learning process to enhance students' scientific literacy.